Assessing a strategy to recover trehalulose sugar from stingless bee honey Geniotrigona thoracica sp. via cation exchange adsorption - Samsol, Muhammad Hairol Ridzwan; Abidin, Zurina Zainal; Zawawi, Norhasnida; Jusoh, Arif Zaidi (Elsevier, 2025)
More than 65 % to 72 % of the rare sugar trehalulose is found in raw stingless bee honey (SBH), and an efficient method for bulk recovery is highly sought. This study investigates the separation of trehalulose from SBH using cation exchange resin (CEA) in batch adsorption mode. Various parameters were optimized to evaluate their effects on adsorption performance. At 15 min, 50 °C, and 1000 g/L honey concentration, 6.34 %, 32.51 % and 33.15 % of trehalulose, glucose, and fructose, respectively, were adsorbed. Trehalulose showed poor adsorption affinity compared to glucose and fructose, leaving most of it in the supernatant solution. With a zeta potential of −3.12 mV, trehalulose exhibited a weak negative charge, contributing to its limited interaction with the cation resin. NMR and FTIR analyses confirmed trehalulose as a sucrose isomer of α-(1 → 1) glucose-fructose glycosidic linkage, containing multiple hydroxyl functional groups, antioxidant, phenolics and reducing sugar properties. The adsorption behaviour was best described by the modified Langmuir model, indicating heterogeneous, multilayer adsorption with high concentration dependency. The pseudo-second-order model suggested that pore diffusion was the rate-limiting step, with the process being endothermic and spontaneous at elevated temperatures. Although cation exchange resin adsorption captures only a small fraction of trehalulose, recovery from the resin is relatively straightforward compared to the more complex process of isolating trehalulose from the sugar-rich supernatant mixture, which poses significant downstream challenges. Thus, selecting a resin that aligns with trehalulose's physicochemical properties is vital for achieving efficient and selective separation.